Both male and female identity influence variation in male signalling effort - Lehtonen TK; Svensson PA; Wong BBM (BIOMED CENTRAL LTD, 2022)
Conclusion: Despite the plasticity in male courtship effort, courtship displays had the potential to reliably convey information about the male to mate-searching females. Our experiment therefore underscores the importance of addressing the different sources contributing to variation in the expression of sexually-selected traits.